2017
DOI: 10.1073/pnas.1703476114
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockin of Dnmt3a R878H initiates acute myeloid leukemia with mTOR pathway involvement

Abstract: DNMT3A is frequently mutated in acute myeloid leukemia (AML). To explore the features of human AML with the hotspot DNMT3A R882H mutation, we generated Dnmt3a R878H conditional knockin mice, which developed AML with enlarged Lin − Sca1 + cKit + cell compartments. The transcriptome and DNA methylation profiling of bulk leukemic cells and the single-cell RNA sequencing of leukemic stem/progenitor cells revealed significant changes in gene expression and epigenetic regulatory patterns that cause differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 30 publications
7
54
0
Order By: Relevance
“…By contrast, these drugs elicited no reduction in OCI-AML3 and OCI AML2 cell viability. However, both OCI-AML2 and OCI-AML3 cells were sensitive to 500 nM sapanisertib, with only 50-60% of cells remaining viable after 48 h ( Figure 7C , 7D ), which was consistent with previous reports [ 19 ]. Kasumi-1 and MOLM13 cells were less sensitive to 500 nM sapanisertib, with about 80% of cells remaining viable after 48 h. The IC50 of inhibitors in these AML cell lines were displayed in Table 2 .…”
Section: Resultssupporting
confidence: 92%
“…By contrast, these drugs elicited no reduction in OCI-AML3 and OCI AML2 cell viability. However, both OCI-AML2 and OCI-AML3 cells were sensitive to 500 nM sapanisertib, with only 50-60% of cells remaining viable after 48 h ( Figure 7C , 7D ), which was consistent with previous reports [ 19 ]. Kasumi-1 and MOLM13 cells were less sensitive to 500 nM sapanisertib, with about 80% of cells remaining viable after 48 h. The IC50 of inhibitors in these AML cell lines were displayed in Table 2 .…”
Section: Resultssupporting
confidence: 92%
“…The most common somatic mutations present in CH are in genes associated with epigenetic modifications, including the DNA methyltransferase DNMT3A , and splicing factors. Several mouse models of DNMT3A -driven CH have been generated by conditional knockout [9], mutant allele knockin [10, 11], or mutant allele overexpression [12]. Further, several studies have identified cooperating mutations that can act synergistically with Dnmt3a knockout or mutation to cause leukemia, such as Flt3 ITD [13, 14], Flt3 ITD and Npm1 c [11], cKit [15], and Kras G12D [16].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, high incidence of DNMT3A mutation was identified in AML and DNMT3A mutation correlated with poor prognosis in AML [ 12 ]. Functional studies showed that DNMT3A was essential for hematopoietic stem cell (HSC) differentiation and mutated DNMT3A initiated AML [ 13 14 ], suggesting DNMT3A acted as a tumor suppressor gene. Although DNMT3B was rarely mutated in AML [ 15 ], studies have proved that loss of DNMT3B accelerated MLL-AF9 leukemia progression and increased expression of DNMT3B in LSC delayed leukemogenesis [ 16 17 ].…”
Section: Introductionmentioning
confidence: 99%